Characterization and small-molecule stabilization of the multisite tandem binding between 14-3-3 and the R domain of CFTR - Stevers, Loes M; Lam, Chan V; Leysen, Seppe F R; Meijer, Femke A; van Scheppingen, Daphne S; de Vries, Rens M J M; Carlile, Graeme W; Milroy, Lech G; Thomas, David Y; Brunsveld, Luc; Ottmann, Christian (Proceedings of the National Academy of Sciences - PNAS, 2016)
Cystic fibrosis is a fatal genetic disease, most frequently caused by the retention of the CFTR (cystic fibrosis transmembrane conductance regulator) mutant protein in the endoplasmic reticulum (ER). The binding of the 14-3-3 protein to the CFTR regulatory (R) domain has been found to enhance CFTR trafficking to the plasma membrane. To define the mechanism of action of this protein-protein interaction, we have examined the interaction in vitro. The disordered multiphosphorylated R domain contains nine different 14-3-3 binding motifs. Furthermore, the 14-3-3 protein forms a dimer containing two amphipathic grooves that can potentially bind these phosphorylated motifs. This results in a number of possible binding mechanisms between these two proteins. Using multiple biochemical assays and crystal structures, we show that the interaction between them is governed by two binding sites: The key binding site of CFTR (pS768) occupies one groove of the 14-3-3 dimer, and a weaker, secondary binding site occupies the other binding groove. We show that fusicoccin-A, a natural-product tool compound used in studies of 14-3-3 biology, can stabilize the interaction between 14-3-3 and CFTR by selectively interacting with a secondary binding motif of CFTR (pS753). The stabilization of this interaction stimulates the trafficking of mutant CFTR to the plasma membrane. This definition of the druggability of the 14-3-3-CFTR interface might offer an approach for cystic fibrosis therapeutics.